2007
DOI: 10.1111/j.1365-2672.2006.03076.x
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation by avian Escherichia coli in relation to media, source and phylogeny

Abstract: Aims:  To assess the abilities of 105 avian pathogenic Escherichia coli (APEC) and 103 avian faecal commensal E. coli (AFEC) to form biofilms on a plastic surface and to investigate the possible association of biofilm formation with the phylotype of these isolates. Methods and Results:  Biofilm production was assessed in 96‐well microtitre plates using three different media, namely, M63 minimal medium supplemented with glucose and casamino acids, brain–heart infusion broth, and diluted tryptic soy broth. Avian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
49
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 27 publications
8
49
1
Order By: Relevance
“…We initially hypothesized that high biofilm formation may be an important phenotype for survival in the soil; however, our results showed that only two soil-persistent isolates produced high levels of biofilm under the conditions investigated, suggesting that the ability to form biofilm may not be an essential phenotype for long-term soil survival. The result of the heterogeneity in biofilm production observed in our study is consistent with the study of Skyberg et al (65), which showed that biofilm production is strain specific and not significantly influenced by phylogenetic group. Similar to previous studies that have shown that biofilm formation is higher at lower temperatures (48,66) and that biofilmrelated genes are upregulated at 23°C compared to 37°C (67), we demonstrate that E. coli strains can produce high levels of biofilm at 15°C.…”
Section: Discussionsupporting
confidence: 82%
“…We initially hypothesized that high biofilm formation may be an important phenotype for survival in the soil; however, our results showed that only two soil-persistent isolates produced high levels of biofilm under the conditions investigated, suggesting that the ability to form biofilm may not be an essential phenotype for long-term soil survival. The result of the heterogeneity in biofilm production observed in our study is consistent with the study of Skyberg et al (65), which showed that biofilm production is strain specific and not significantly influenced by phylogenetic group. Similar to previous studies that have shown that biofilm formation is higher at lower temperatures (48,66) and that biofilmrelated genes are upregulated at 23°C compared to 37°C (67), we demonstrate that E. coli strains can produce high levels of biofilm at 15°C.…”
Section: Discussionsupporting
confidence: 82%
“…To examine whether the T6SS was involved in biofilm formation or not, wild-type and mutant strains were tested for their ability to form biofilms on polystyrene surfaces as previously described (41,42). The growth rates of T6SS-associated mutants were similar to those of the wild-type strain (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3A). Since most virulence factors contributing to biofilm formation could induce intercellular autoaggregation (42), it could be inferred that the inactivation of T6SS1 reduced autoaggregation of APEC strain TW-XM. However, T6SS2 did not affect the biofilm formation.…”
Section: Resultsmentioning
confidence: 99%
“…A close relationship between virulence factors and pathogencity of APEC has been reported (Babai et al, 1997;Gomis et al, 2001;Janben et al, 2001;Kaipainen et al, 2002;Dziva & Stevens, 2008;Tyler et al, 2008). Genotyping of the virulence-associated genes has been suggested to differentiate APEC strains isolated from internal organs of poultry suffering multi-systemic infections from E. coli strains from faeces of clinically healthy chickens (Pfaff-McDonough et al, 2000;Delicato et al, 2003;McPeake et al, 2005;Rodriguez-Siek et al, 2005b;Skyberg et al, 2007;Johnson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%